Distribution of glyphosate‐resistant Amaranthus spp. in Nebraska. Issue 10 (9th January 2018) - Vieira, Bruno C; Samuelson, Spencer L; Alves, Guilherme S; Gaines, Todd A; Werle, Rodrigo; Kruger, Greg R
Abstract: BACKGROUND: Palmer amaranth ( Amaranthus palmeri S. Wats.), common waterhemp ( Amaranthus tuberculatus var. rudis ), and redroot pigweed ( Amaranthus retroflexus L.) are major weeds occurring in fields throughout Nebraska with recurrent grower complaints regarding control with glyphosate. The objective of this study was to investigate the frequency and distribution of glyphosate‐resistant Palmer amaranth, common waterhemp, and redroot pigweed populations in Nebraska. The study also aimed to investigate how agronomic practices influence the occurrence of glyphosate resistance in the three Amaranthus species. RESULTS: Glyphosate resistance was widespread in common waterhemp (81% of the screened populations), few Palmer amaranth populations were glyphosate‐resistant (6% of the screened populations), whereas no glyphosate‐resistant redroot pigweed populations were identified in Nebraska. Weed species, geographic region within the state, and current crop were the most important factors predicting the occurrence of glyphosate resistance in fields infested with Amaranthus species in Nebraska. CONCLUSION: The intensive glyphosate selection pressure exerted in soybean ( Glycine max ) fields in eastern Nebraska is one of the major factors causing widespread occurrence of glyphosate resistance in common waterhemp in the state. The relatively low frequency of glyphosate‐resistant Palmer amaranth in the state highlights the importance of the application timing and the adoption of multiple modes of action in weed management practices to delay the evolution of glyphosate resistance. © 2017 Society of Chemical Industry Abstract : Weed species, geographic region within the state, and current crop were the most important factors predicting the occurrence of glyphosate resistance in fields infested with Amaranthus species in Nebraska.